2004
DOI: 10.1001/archpedi.158.11.1070
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Lung Function 20 Years After Wheezing in Infancy

Abstract: The increased risk for asthma persists until adulthood after bronchiolitis in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
150
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(169 citation statements)
references
References 33 publications
15
150
0
4
Order By: Relevance
“…They comprised 6 birth cohorts [17][18][19][20][21][22] and 19 population-based longitudinal studies. [12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Tables 1 and 2 give an overview of the included studies. The reasons for rejecting the remaining 30 papers [9,10, are summarised in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They comprised 6 birth cohorts [17][18][19][20][21][22] and 19 population-based longitudinal studies. [12,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Tables 1 and 2 give an overview of the included studies. The reasons for rejecting the remaining 30 papers [9,10, are summarised in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Two combinations which included early childhood infection had very wide confidence intervals (ID 43 & 45) suggesting there were other unexplored confounding factors contributing to the observed differences. In some studies early respiratory viral infections have been associated with the subsequent development of asthma [23,32,34,36] but not in others. [40,74] It has been suggested that RV infections in early life are more likely to cause reduced lung function than RSV infections.…”
Section: Page 13 Of 24mentioning
confidence: 99%
“…Ongoing birth cohort studies should be able to provide information on the outcome in general populations during the 2010s. Considering more severe early wheeze, half of the children hospitalised with acute wheeze before the age of 2 yrs were symptom-free by the age of 5 yrs and 70% by 10 yrs, but only 57% by 17-20 yrs [44][45][46], illustrating the tendency for relapse during adolescence. Female sex, passive smoking during infancy and early sensitisation to allergens were risk factors for symptoms continuing into early adulthood, but type of virus and premature birth were not.…”
Section: Multiple-trigger Wheezementioning
confidence: 99%
“…14% to 40% of bronchiolitis patients will eventually have asthma [25,196], with the association persisting into adulthood [196][197][198][199][200][201][202][203]. In young children, asthma is heralded by acute bronchiolitis in 90% of cases, one third of which require hospitalization [204].…”
Section: Predicting Whether a Bronchiolitis Patient Will Later Be Diamentioning
confidence: 99%